Kecemasan Mahasiswa Fakultas Dakwah Menghadapi Dunia Kerja - Haryati Haryati; Neneng Hasanah (INNOVATIO: Journal for Religious Innovation Studies, 2019)
This paper is motivated by research related to the anxiety felt by students of the Da'wah Faculty in facing the world of work. facing the working world, students need social support from the surrounding environment to reduce this anxiety. The relationship between social support and student anxiety in facing the world of work through a quantitative approach with multiple correlation methods. Non-Probability Sampling technique, Accidental Sampling technique is used in sampling. The research subjects were 101 students of the dakwah faculty, batch 2016. Based on the results of the research analysis, the correlation was 0.472 with a significance value of 0.000 (p <0.05). The results of the pearson correlation> r table are 0.472> 0.195, thus the research shows that the research hypothesis is accepted. (Ho is accepted, and Ha is rejected). so that there is a relationship between social support and student anxiety in facing the world of work in students of the Da'wah Faculty of the State Islamic University of Sulthan Thaha Saifuddin Jambi. With a pearson correltion value of 0.472, this indicates a strong correlation (correlation) between social support and student anxiety in facing the world of work. Tulisan ini dilatarbelakangi oleh penelitian berkaitan kecemasan yang dirasakan oleh mahasiswa Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi dalam menghadapi dunia kerja. menghadapi dunia kerja mahasiswa membutuhkan dukungan sosial dari lingkungan sekitar untuk mengurangi kecemasan tersebut. Hubungan antara dukungan sosial dengan kecemasan mahasiswa dalam menghadapi dunia kerja melalui pendekatan kuantitatif dengan metode korelasi multiple. Teknik Non-Probability menggunakan teknik Accidental Sampling digunakan dalam penarikan sampel. Subjek penelitian 101 mahasiswa fakultas dakwah angkatan 2016. Berdasar hasil analisis penelitian hasil korelasi sebesar 0,472 dengan nilai signifikansi sebesar 0,000 (p < 0,05). Hasil pearson correlation > rtabel sebesar 0,472 > 0,195, dengan demikian penelitian menunjukkan bahwa hipotesis penelitian diterima. (Ho diterima, dan Ha ditolak). sehingga terdapat hubungan antara dukungan sosial dengan kecemasan mahasiswa dalam menghadapi dunia kerja pada mahasiswa Fakultas Dakwah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. Dengan nilai pearson correltion sebesar 0,472 hal ini menunjukkan adanya hubungan (korelasi) antara dukungan sosial dengan kecemasan mahasiswa dalam menghadapi dunia kerja yang cukup kuat.